2017
DOI: 10.1002/mabi.201600523
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Scaffold Cell Adhesion Using Artificial Membrane Binding Proteins

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms FIGURE FOR ToC_ABSTRACT3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Surface chemistry, topography, chemical composition, wettability, stiffness, dimensionality, porosity, and degree of cross‐linking are fundamental parameters that must be taken into the account in the design of substitute for medical applications . By manipulating surface properties of implants such as surface charge, functional groups, and topography, initial cell attachment can be tuned in a controlled manner …”
Section: Effects Of Surface Properties On Cellular Behaviorsmentioning
confidence: 99%
“…Surface chemistry, topography, chemical composition, wettability, stiffness, dimensionality, porosity, and degree of cross‐linking are fundamental parameters that must be taken into the account in the design of substitute for medical applications . By manipulating surface properties of implants such as surface charge, functional groups, and topography, initial cell attachment can be tuned in a controlled manner …”
Section: Effects Of Surface Properties On Cellular Behaviorsmentioning
confidence: 99%
“…These include, a reduction in risk arising from oncogenesis in the therapeutic cells, minimal impact on the cell manufacturing process as the modification step can be readily integrated into an existing therapeutic pipeline, the display number per cell can be systematically varied to reduce the risks associated with patient-specific expression levels, and protein production is scalable and can be produced using good manufacturing practice procedures. 103,104 An excellent example of direct protein-based membrane modification was demonstrated by Won et al, who displayed recombinantly produced CXCR4 on MSC membranes using lipid-PEG vesicles (Figure 2A). 105 They demonstrated that CXCR4 was only present in the MSCs membrane after delivery by confocal microscopy studies without affecting the viability of MSCs and showed up to a twofold improvement in their migration toward SDF-1 following a concentration gradient in vitro.…”
Section: Protein-based Membrane Modificationsmentioning
confidence: 99%
“…Direct protein‐based membrane modification strategies provide transient display of the targeting construct and present a number of potential benefits over generic approaches for improved cell homing. These include, a reduction in risk arising from oncogenesis in the therapeutic cells, minimal impact on the cell manufacturing process as the modification step can be readily integrated into an existing therapeutic pipeline, the display number per cell can be systematically varied to reduce the risks associated with patient‐specific expression levels, and protein production is scalable and can be produced using good manufacturing practice procedures 103,104 …”
Section: Approaches For Improving Sc Homing and Retentionmentioning
confidence: 99%
“…This can be related with the functionality changes induced by the EF at different intensities, namely the increase of the contact angle, swelling, porosity, degradation rate and elastic behaviour of the scaffolds. The changes in surface properties may facilitate the adhesion of the cells to the matrix, once electrostatic and hydrophobic contributions play a decisive role in such phenomenon [37,44]. Higher swelling and porosity also facilitate the proliferation and dispersion of the cells, as well as allow a better in and out-flow of nutrients, metabolites and gas exchanges [15,38].…”
Section: Cell Viability and Proliferationmentioning
confidence: 99%